Assessment of brain activation regulation in first graders via RAN / RAS test - Tatiana V. Akhutina; Elena A. Pronina (Национальный психологический журнал, 2015)
RAN / RAS test (Rapid Automatized Naming / Rapid Alternating Stimulus) has been used successfully used by many psychologists, primarily to predict the risk of dyslexia, as it includes a language component and requires good visual-verbal connections. However, The research demonstrates that the low speed of naming is an effective indicator of neurocognitive problems of information processing as a whole (learning difficulties in general), not just reading difficulties. This can be explained in two ways: disturbance of executive mental control and the difficulties of automatization: the difficulties of the transition from a controlled energy-consuming assignment to a less energy-consuming one. The second interpretation describes the problems of energy resources of cognitive functioning. It is similar to weak maintenance of cortical structures activation. However, using the test mentioned herewith for assessing functions of activation regulation has not been described previously. In terms of the Luria’s three functional units of the brain theory the RAN / RAS test can be considered as sensitive to the weakness of the first unit, whose function is to maintain the activity of cortical structures. So the aim of the research is to prove the possibility of assessing the activation regulation using the RAN / RAS test. This issue is relevant because neuropsychological tools for determining the weakness of Unit I functions are not quite sufficient, while the problem of “energetic” unit ranks first in the frequency of occurrence in children with learning disabilities.